Effects of nitrous acid exposure on baseline pulmonary resistance and Muc5ac in rats. (16th April 2018) - Ohyama, Masayuki; Horie, Ichiro; Isohama, Yoichiro; Azuma, Kenichi; Adachi, Shuichi; Minejima, Chika; Takenaka, Norimichi
Abstract: We examined the baseline pulmonary resistance (RLung), baseline dynamic lung compliance (Cdyn), cytokine inductions, and histological alterations in rats exposed to nitrous acid (HONO) with secondary products of nitrogen dioxide (NO2 ) and nitric oxide (NO) to assess its biological effects. We exposed three groups of nine male F344 rats to different doses of HONO for six weeks (24 h/day). The cumulative values of HONO concentration were measured twice. The average concentrations of nitrogen oxide for each group were 5.8 parts per million (ppm) HONO with secondary products of 0.7 ppm NO2 and 2.3 ppm NO, 4.1 ppm HONO with 0.1 ppm NO2 and 0.6 ppm NO, and a clean air control. We measured baseline RLung and baseline Cdyn using tracheal cannulation. A tracheal tube was inserted into the trachea by tracheostomy, and lung function measurements (baseline RLung and baseline Cdyn) were conducted in mechanically ventilated rats. We measured mRNA levels of Cxcl-1, TNF-α, and Muc5ac in the right lung using quantitative RT-PCR, and observed histological alterations and the alveolar mean linear intercept (Lm) on the left lung. Our results demonstrated that HONO exposure significantly increased baseline RLung, Lm and Muc5ac expression, but did not affect baseline Cdyn or expression of Cxcl-1 and TNF-α. Further, we identified bronchial smooth muscle hypertrophy, pulmonary emphysema-like alterations in the alveolar duct centriacinar regions, and increased goblet cells in HONO-exposed rats. The present results suggest that HONO (with secondary products) adversely affects respiratory function, but that these pathologies may be unrelated to inflammation.